2021
DOI: 10.1155/2021/5196190
|View full text |Cite
|
Sign up to set email alerts
|

Image Recommendation Algorithm Combined with Deep Neural Network Designed for Social Networks

Abstract: In recent years, deep neural networks have achieved great success in many fields, such as computer vision and natural language processing. Traditional image recommendation algorithms use text-based recommendation methods. The process of displaying images requires a lot of time and labor, and the time-consuming labor is inefficient. Therefore, this article mainly studies image recommendation algorithms based on deep neural networks in social networks. First, according to the time stamp information of the datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Classifiers based on linear representations have been widely used in many fields. Building on these observations, Du et al suggested a new competitive and categorization via cooperative representation that uses properties of training data with L2 parametric regularization to create a competitive environment that allows the correct class to contribute more to the encoding [14]. Chi et al proposed a new CRC-based classifier utilizing class-mean weighted discriminative corepresentation [15].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Classifiers based on linear representations have been widely used in many fields. Building on these observations, Du et al suggested a new competitive and categorization via cooperative representation that uses properties of training data with L2 parametric regularization to create a competitive environment that allows the correct class to contribute more to the encoding [14]. Chi et al proposed a new CRC-based classifier utilizing class-mean weighted discriminative corepresentation [15].…”
Section: Related Workmentioning
confidence: 99%
“…In equation 4.4, P o k (c m |M ) is the likelihood that an element will appear in the occurrence M and P o k (M ) is the likelihood that a consumer will like a product. The likelihood that a user would adore a product when the user features is shown in equation (14).…”
Section: A Cf-based Book Recommendation Model For University Librariesmentioning
confidence: 99%
“…The algorithm sorted user interaction records over time, combined feature algorithms to construct feature vectors, and constructed a long and short term memory (LSTM) neural network. Results showed that LSTM's performance was superior to traditional social network image recommendation algorithms [4]. To enhance the recommendation accuracy, scholars like Fang J proposed a Collaborative Filtering recommendation algorithm that leverages deep neural network fusion.…”
Section: Related Workmentioning
confidence: 99%
“…To address the shortcomings of the overall network random sampling prediction method, a relationship prediction method with random sampling in colleges and universities is proposed as the CCS prediction algorithm. [27] e CCS algorithm is applicable to networks where all college information is known and the college structures do not overlap. When a node belongs to more than one college at the same time, it is grouped into the college with the higher number of relationships among nodes.…”
Section: Ccs Algorithmmentioning
confidence: 99%